Pengaruh Harga Lokasi Fasilitas Dan Promosi Terhadap Kepuasan Konsumen Pada Perumahan Villa Pertiwi - Nst, Rizli Muktar (Universitas Labuhanbatu, 2021)
The purpose of this study was to determine the effect of price, location, facilities and promotions on consumer satisfaction in villa pertiwi housing either partially or simultaneously. Data collection using interviews, questionnaires and literature studies. Execution of data analysis methods using the help of software SPSS 16.0 for Windows. This study used a sample of 40 employees taken using census techniques. The results based on the test simultaneously (test F) showed that simultaneously (simultaneously) price (X1), location (X2) facilities (X3) and promotion (X4) affect consumer satisfaction (Y) housing Villa pertiwi,. where the value Fcount (477,687) > Ftable (2.63) with probability 0.000< 0.05. The results of partial hypothesis testing (t test) showed that the price (X1) has a positive and significant effect on consumer satisfaction (Y) Villa Pertiwi housing where the value of thitung (6.149) > ttable (1.689) with a probability of 0.000< 0.05; location (X2) positive and significant effect on customer satisfaction (Y) housing Villa Pertiwi., where the value of thitung (8.728) > ttable (1.689) with a probability of 0.000< 0.05; facilities (X3) positive and significant effect on customer satisfaction (Y) housing Villa Pertiwi, where the value of thitung (21.980) > ttable (1.689) with a probability of 0.001< 0.05. promotion (X4) positive and significant effect on customer satisfaction (Y) housing Villa Pertiwi, where the value of thitung (2095) > ttable ( 1689) with a probability of 0.001 < 0.05. The value of Adjusted R Square indicates that consumer satisfaction can be explained by price,location, facilities and promotions while the remaining 2.0% can be explained by other factors that are not examined in this study.